2010
DOI: 10.1007/s11136-010-9777-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Parkinson’s disease patients: validation of the Short-Form Eight-item Parkinson’s Disease Questionnaire (PDQ-8) in Taiwan

Abstract: The results of this study suggest the PDQ-8 is a valid and reliable disease-specific health-related quality-of-life instrument for Parkinson's disease in Taiwan when used independently of the PDQ-39.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
6
8
0
Order By: Relevance
“…To our knowledge, this was the first study to evaluate the PDQ-8 in mainland China longitudinally with a large sample. Our results showed good validity and reliability of the Chinese version PDQ-8, in accordance with other validation studies [ 8 , 22 ]. There was no floor or ceiling effect of the PDQ-8-SI and the PDQ-39-SI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this was the first study to evaluate the PDQ-8 in mainland China longitudinally with a large sample. Our results showed good validity and reliability of the Chinese version PDQ-8, in accordance with other validation studies [ 8 , 22 ]. There was no floor or ceiling effect of the PDQ-8-SI and the PDQ-39-SI.…”
Section: Discussionsupporting
confidence: 91%
“…In China, the PDQ-39 has been translated and validated by Tsang KL et al [ 7 ]. An evaluation of the Chinese version of PDQ-8 has been conducted in Taiwan with cross-sectional design and a relatively small sample size [ 8 ]. A different Chinese version of the PDQ-8 was also validated with promising results in Singapore [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 5, the item-to-scale internal consistency of the Persian PDQ-8 is within the acceptable range compared to other reports. Generally, the independent Persian version of the PDQ-8 showed acceptable internal consistency, which is in line with the other studies using the independent PDQ-8 [7,28]. …”
Section: Discussionsupporting
confidence: 90%
“…The Cronbach’s alpha coefficient was estimated to be lower than 0.9 in all studies (between 0.72 and 0.88), which is almost lower than PDQ-39 in different reports. Our Cronbach’s alpha estimate (0.74) is quite similar to the Greek (0.72) [10], Italian (0.72) [24] and English version in Canadian (0.72) [25] and Singaporean (0.75) [9] populations while some other studies showed higher alpha coefficients [7,26-28]. As shown in Table 5, the item-to-scale internal consistency of the Persian PDQ-8 is within the acceptable range compared to other reports.…”
Section: Discussionsupporting
confidence: 73%
“…PDQ 39 covers eight aspects of quality of life including mobility, activities of daily living, emotional wellbeing, stigma, cognition, communication and bodily discomfort (Jenkinson et al, 1997). PDQ 39 also is translated in forty languages (Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%